Gostota lesa - metode določanja in pomen pri razvoju gozdno lesnega biogospodarstva - Arnič, Domen (Acta silvae et ligni, 2021)
Wood density is an important physical property that can be easily measured and is closely related to many other wood properties. Furthermore, wood density is a good indicator of the usability and applicability of wood in the wood processing, construction and energy industries. Because it is strongly dependent on moisture content and porosity, there are various definitions of wood density in the literature, among which the density measured on the basis of dry matter and volume is the most commonly used. The aim of this paper is to present different methods for wood density determination and the importance of collecting such data for the development of the forest-based bioeconomy. In practice, there are several direct and indirect methods of density measurement; in addition to the most basic volumetric approach, the density of wood can be measured by penetrometer, resistograph, high frequency densitometry, X-rays, near infrared spectroscopy and microwaves. Wood will continue to grow in importance, as it is one of the key raw materials for the transition to a sustainable bioeconomy. The accurate and timely determination of wood density allows for the appropriate distribution and direction of flows of this raw material between individual conventional and new sectors (areas of use) and thus its more efficient and sustainable use.
Keywords: forest-based bioeconomy; gostota lesa; gozdno lesno biogospodarstvo; high frequency densitometry; lastnosti lesa; penetrometer; rentgenska denzitometrija; resistograph; rezistograf; visokofrekvenčna denzitometrija; wood density; wood properties; X-ray densitometry